Confronting Gender-Based Violence in Nigerian Higher Institutions: Creating Safe and Inclusive Campuses as an Imperative for Educational Transformation - Angela Nkiru Nwammuo; Esemena Jeroh; Njideka Gloria Ikegbusi; Angela Nkiru Nwammuo; Esemena Jeroh; Njideka Gloria Ikegbusi; Justina Oboreh; Justina Oboreh (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2027)
Gender-based violence (GBV) could be describes as a pervasive issue that remains systematically under addressed and under-reported within the Nigerian higher education system. This menace, no doubt, is exacting severe consequences on student wellbeing, academic performance, institutional reputation, and national human capital development. This paper examines the nature, prevalence, drivers, and multi-dimensional implications of GBV across Nigerian tertiary institutions and used Feminist Theory, particularly gender power theory as articulated by Connell (2005)., Institutional Theory (DiMaggio & Powell, 1983) and Communication Theory, particularly Habermas's (1984) theory of communicative action, as theoretical frameworks. Drawing on empirical studies, the theoretical frameworks, and existing legal and policy instruments, the paper identifies sexual harassment, peer-based violence, and institutional silence as dominant manifestations of GBV, while locating their persistence in entrenched patriarchal norms, asymmetrical power relations, rapid institutional growth outpacing governance capacity, and chronically weak enforcement mechanisms. Adopting a communication-driven, multi-sectoral analytical orientation, the paper proposes strategic pathways toward safe and inclusive campuses, encompassing strengthened anti-GBV policies, anonymous survivor-centred reporting systems, gender-responsive curricula, technology-enabled advocacy, community partnerships, and transformational leadership commitment. The paper argues that most higher institutions in Nigeria, like Southern Delta University, Ozoro, Delta State, by virtue of their developmental trajectory, are uniquely positioned to institutionalise gender equity from inception, rather than as corrective retrofit. It concludes that creating safe campuses is not merely a moral imperative but a strategic prerequisite for sustainable higher education and national socio-economic development in Nigeria.